On Sample Size and Quick Simultaneous Confidence Interval Estimations for Multinomial Proportions - KWONG, Koon Shing (Institutional Knowledge at Singapore Management University, 1998)
Asymptotically, sample proportions from a multinomial distribution converge in distribution to a multivariate normal distribution with a singular negative product correlation structure. Based on this result, we propose a new approach to estimate the sample size requirement for constructing quick simultaneous confidence intervals (QSCI) for multinomial proportions. In addition, this new approach can be used to construct QSCI and provides a statistical justification to the reports of the opinion polling.